SMARS-I: smart material actuated robotic snake (Ver-1) - Billah, Md. Masum; Khan, Md. Raisuddin; Shafie, Amir Akramin (Elsevier, 2016)
In this research, a snake robot is developed using Ionic Polymer Metal Composite (IPMC), one of the best artificial muscles from Electro-active Polymer (EAP) group. A novel tendon driven parallel structure is built for a single link of the snake robot. A kinematic analysis has been discussed of the actuator following with the analysis of the IPMC artificial muscle. There are some exceptional characteristics of this snake robot, such as, perform 3DOF motion in a single joint, perform flexible motion, light weight. These special characteristics enhance the snake robot to operate in hazardous area for disaster recovery mission.